Diet quality and hearing loss among middle–older aged adults in the USA: findings from National Health and Nutrition Examination Survey. Issue 5 (31st October 2019) - Huang, Qiushi; Jin, Yichen; Reed, Nicholas S; Ma, Yan; Power, Melinda C; Talegawkar, Sameera A
Abstract: Objective: To examine the associations between overall diet quality and hearing function among middle–older aged adults in the USA. Design: Cross-sectional analysis. Diet quality was examined using the Mediterranean Diet Score (MDS), using data from a single 24 h dietary recall. Hearing function was objectively measured by audiometry assessments and hearing loss, including high- and low-frequency hearing loss, was defined as pure-tone averages at specific ranges of hearing frequencies >25 dB. Weighted logistic regression analyses were performed to examine the associations of MDS (scored 0–9, categorized at the median as ≤3 or >3) with hearing loss and high- and low-frequency hearing loss. Setting: National Health and Nutrition Examination Surveys 2000–2006 and 2009–2012. Participants: Adults aged ≥50 years ( n 1639) with valid dietary and audiometry assessments. Results: After adjusting for potential confounders, a non-significant trend for a protective association of higher MDS was observed for hearing loss (OR = 0·78; 95 % CI 0·49, 1·23). A significant inverse association was observed for high-frequency hearing loss (OR = 0·64; 95 % CI 0·43, 0·95). No association was found for low-frequency hearing loss among women; however, higher MDS was significantly associated with higher odds of low-frequency hearing loss among men (OR = 2·63; 95 % CI 1·39, 4·95). Conclusions: Among middle–older aged adults, adherence to a Mediterranean-style diet was inversely associated with hearing loss, including those at high hearing frequencies, among older adults. However, a detrimental association was observed at low hearing frequencies among men. Future investigations with a longitudinal design are needed to clarify the associations between diet quality and hearing loss.